Knockdown of miR393 Promotes the Growth and Biomass Production in Poplar - Chu, Liwei; He, Xuejiao; Shu, Wenbo; Wang, Lijuan; Tang, Fang (Frontiers in Plant Science, 2021)
Short Tandem Target Mimic (STTM) which is composed of two short sequences mimicking small RNA target sites, separated by a linker of optimal size, can block the functions of all members in a miRNA family. microRNA393 (miR393), which is one of the conserved miRNA families in plants, can regulate plant root growth, leaf development, plant architecture and stress resistance. In order to verify the role of miR393 in secondary growth of trees, we created its STTM transgenic poplar lines (STTM393). The expression of miR393 in STTM393 lines was reduced by over 10 times compared with the control plants. STTM393 lines showed promoted growth with about 20% higher, 15% thicker, and 2-4 more internodes than the control plants after 3-month in growth. Cross section of the stems showed STTM393 lines had wider phloem, xylem and more cambium cell layers than control plants, and the lignin content in STTM393 lines was also higher as revealed by staining and chemical determination. Based on the transcriptome analysis, the genes related to auxin signaling pathway, cell cyclin, cell expansion and lignin synthesis had higher expression in STTM393 lines than that in control plants. The higher expression levels of FBL family members suggested the auxin signaling pathway was strengthened in STTM393 lines thus to promote the plant growth. Therefore, knockdown of miR393 using STTM approach provides a way to improve poplar growth and biomass production.